Identifying the Gap between Lecturer Competencies and Student Learning Outcomes in the Challenging Era of the 21st Century - MAS, SITTI ROSKINA; SARYANTO; ILI, LA; RAHMAT, STEPHANUS TURIBIUS; HENDRIARTO, PRASETYONO (The journal of contemporary issues in business and government, 2021)
This study discuss efforts to bridge the gap between the competency of applying lecturer technology and student learning outcomes in the 21st century, an era full of challenges and global job market competition. We started this discussion by collecting data from literary sources and international publications. Then proceed with a narrative qualitative analysis involving a coding system, critical evaluation, and concluding by fulfilling the principles of the validity and reliability of the findings. We conducted data searches with the journal Google Doc, Google Scholar, and Eric with various publications from 2010 to 2020. We also analyzed learning strategies and techniques, as well as evaluation approaches. We find that most lecturers' papers have very low teaching technology competence to current standards in backing up their teaching and research. The paper offers solutions and ideas approaches to support active student learning activities with various techniques, methods, and technology-based learning exploration activities, up to date. Some publications offer lecturers an academic work approach that is effective in research-based learning; reduce the traditional lecturing approach, which often hinders the accelerated process of conceptual understanding and application of core content and useful advice to lecturers and students. Several papers also advise on specific college-style learning solutions that are different from school student learning. Finally, this study's results will be useful input for improving student learning in the digital era, which is full of global competition, and for developing higher education curricula.